Groundwater Management and Resources - Kalantar, Bahareh (IntechOpen, 2021)
This book discusses theoretical and technical innovations in water resource management. Chapters cover such topics as groundwater recharging technology, cumulative groundwater impact assessment, depletion and deterioration of groundwater, and identification of water inrush using various multiple non-linear machine learning models. Also discussed are the evaluation of rainfall time series and the use of fractal analysis. Finally, the book contains information on the governance crisis and governability of the use of groundwater in arid zones.